THE EFFECT OF CLAY-MADE GRANULES MATERIAL ON THE VEGETABLES HYDROPONIC GROWTH WITH WICK SYSTEMS - Iis Marlina; Sugeng Triyono; Ahmad Tusi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This study aimed to determine the effect of granule growing media on growth and yield of vegetables in ahidroponic wick system. The design of this study used Randomized Complete Block (RCB) with factorialarrangement and three replications. The first factor consisted of three levels : kale (S1), spinach (S2), andmustard (S3). The second factorwere the size of the granules with four levels : 12mm (M1), 6mm (M2), 4 mm(M3) and husk char (M4) as a control. Each plant was grown in a wicked pot. There were 12 treatmentcombinations, with three replicates. Parameters observed were physical properties of the media,evapotranspiration, number of leaves, growth, biomass, and yield. Data was analyzed using the Analysis ofVariance (ANOVA) 1%and 5%levels of significance, followed by LSDcomparision. Results showed that therewasno significant interaction betweenmedia and types of plant. However; sizes of media significantly affected theevapotranspiration, growth, biomass, and yield.Keywords:Wicked, hydroponics, granules, media, vegetables